Analisis Tingkat Akurasi Model Backpropagation Dalam Prediksi Indeks Pembangunan Manusia (IPM) di NTB - Mila Haryati; Rosdiana Rosdiana; Khaerunnisa Khaerunnisa; Okta Widya Arsani; Mufti Wahyudi (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2019)
This study aims to determine the type of training in the most accurate Artificial Neural Network (ANN) in the Backpropagation method which was applied using matlab. In the simulation, the authors used the Human Development Index (HDI) data in the Province of West Nusa Tenggara (NTB) in 2010-2018 to predict the Human Development Index (HDI) data in West Nusa Tenggara (NTB) in 2019. Artificial neuralism with the Backpropagation method valued are Traingd, Traingdx, And Trainrp with the accuracy of each type of training algorithm using MSE. Based on the simulation results, the data uses Traingd, Traingdx, And Trainrp which can be used to assess the most popular regression in graph 1 Traingd with a value of R = 0.99744. Producing output from Traingd results Caused by the Human Development Index (HDI) data in 2019. The results of the predictions of ten districts / cities in 2019 in West Nusa Tenggara are 66,791, 65.2014, 65.2769, 67.0017, 67.3496, 66.0761, 72.2184, 64.8257, 78.3422, 76,618 and with error values of 0.29092, -0.13139, -0.07693, -0.73169, -0.53963, -0.50668, -1.8084, -0.68567, 0.38785, -1.768.